The Modus Medendi and the Benedictine Order in Anglo-Norman England - Dawtry, Anne F. (Studies in church history, 1982)
The Benedictines played an important part in the development of medicine in England between 1066 and 1215. In pre-conquest England, the care of the sick had been based upon little more than the practices of Anglo-Saxon leeches which were largely founded upon superstition. Botany had become a drug list and medicine had deteriorated into little more than a collection of formulae. After the Norman conquest, chiefly through the influence of Benedictine scholars from the continent, medical learning in England began to be based upon the writings of the ancient world. These included not only the works of Galen and Hippocrates but also anonymous medical treatises in Latin such as the De Modo Medendi.